The Pathogenesis of Pseudorabies in Mice: Virus Replication at the Inoculation Site and Axonal Uptake - Field, H. J.; Hill, T. J. (Journal of General Virology, 1975)
SUMMARY Three-week-old mice were inoculated in the right ear pinna with pseudorabies virus. Ears were surgically removed at various times after inoculation and changes from the normal pathogenesis were observed. Virus replication in the ear tissue and cervical dorsal root ganglia was also monitored. Following inoculation with a small dose of virus, local multiplication of the virus was necessary before the infection spread to the nerves. With larger infecting doses there was probably direct uptake of virus from the inoculum into the nerve endings. After these larger doses virus was first detected in the dorsal root ganglia 17 h after infection, suggesting a retrograde axonal flow rate of at least 1.7 mm/h.